CONSEQUENCES OF INCOMPLETE REASONING IN COURT ORDER FOR COVERT MEASURES (EU and comparative law issues and challenges series (ECLIC), 2020)
After several decisions of the European Court of Human Rights (ECtHR) against Croatia because of incomplete reasoning in a court order for covert measures (cases Dragojević, Bašić, Matanović and Grba), statutory regulations were not amended, but in the case-law an attempt was made to change the interpretation regarding exclusion of gathered evidence. The author researches this issue in order to determine the trends in the Supreme Court’s (SC) interpretation, and impact of the ECtHR case-law over the past 12 years (N=67). The results show that for a long time the SC has argued that a deficiency in reasoning is an irregularity, but not as serious to lead to exclusion of covert recordings and other evidence. One of the SC chambers issued a decision in 2017, which it called “the revision”, in which it expressed a different view that it was necessary to exclude all evidence gathered using incomplete court order, referring to some rules in few ECtHR decisions. The author therefore analyses the ECtHR’s rules on the judicial review, the exclusion of illegal evidence, and other available safeguards to reduce court arbitrariness. The results indicate that exclusion of evidence is not primary remedy for improving lawfulness of procedure. Problems with compliance with the Convention law could continue to arise due to a lack of other appropriate safeguards in Croatian legislature.